ANALISIS PEMELIHARAAN MESIN POMPA PULP MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE - Fadli Perdana Yuda; Muhammad Ihsan Hamdy; Harpito; Suherman; Rika Taslim (JURNAL PERANGKAT LUNAK, 2024)
Implementing a maintenance system in production has a strategic role in maintaining machine performance and preventing bottlenecks. This research focuses on pulp pump machine maintenance problems in paper mills, which cause time delays and decreased performance. The Pulp Pump Machine consists of three machines, including the 924 U 404 Pulp Machine Pump Unit, the 825 M 576 Pulp Machine Pump Unit, and the 825 M 550 Pulp Machine Pump Unit. Lack of intensive maintenance results in component damage such as leaking mechanical seals, oil seals that often leak, loose bearings, and impeller wear. As a result, the machine does not operate optimally, produces defective products, and is detrimental to the company. This research aims to identify critical components and recommend actions using the Reliability Centered Maintenance (RCM) approach. Pump Unit 924 U 404 Pulp Machine showed the largest contribution to damage, reaching a total of 33 incidents (50%). Pulp pump machine components include bearings, mechanical seals, wear rings, shafts, vanes and impellers. From the FMEA calculations, the highest ranking results were obtained, namely the Shaft component with an RPN value of 240, then Bearings with an RPN value of 200, Vane with an RPN value of 192. From the LTA (Logic Tree Analysis) analysis there are 3 critical components, namely shaft, bearing, and vane. The selected distribution uses a normal distribution with the recommended action selected, namely Time Directed (TD).